A conceptual framework for personality modelling in correlation with EEG-based a affect - Alarabi, Khamis Faraj; Abdul Rahman, Abdul Wahab; Zulkifli, M. A.; Kamaruddin, Norhaslinda (2017)
It is well known that people are naturally different and behave differently even in the given similar situations. Each individual has unique characteristic patterns of personality traits that derive and control his/her behavior. However, someone's behavior can be predicted by assessment his/her personality. Therefore, personality tests have become increasingly popular in business, education, and medicine as well. The traditional way for measuring someone's personality has been through interviews or self-reported questionnaires. Such measurements depend on human behavior and can be affected by factors such as environment, subjectivity, and cultural biasness. Therefore, this paper introduces a conceptual framework for measuring personality from brain waves which are independent of the intended human behavior. Some studies have reported that behavior is highly influenced by emotions and emotions play a crucial role in causing it. On the other hand, psychologists have reported strong qualitative correlation between personality dimensions and affect dimensions specifically emotional valence and arousal. Studies have also reported that affect dimensions can be measured from brain signals by using emotion recognition systems. The main idea of this framework is to measure personality dimensions using personality test and to measure emotions from brain signals, then quantifying the correlation between personality dimensions and basic emotions primitives. The significant correlation can be then used for predicting personality factors.